Methodology - who needs it? - Hammersley, Martyn ([Thousand Oaks, Calif. : SAGE], 2011)
The speaker states that there are two kinds of methodology, one being as technique and the other philosophy.
Online video.
Includes transcript.
Specialized.
Description based on online resource; title from home page (viewed on Feb. 4, 2012).
Keywords: elektronické knihy; electronic books; Research -- Evaluation; Methodology